Information, ingestion, and impulsivity: The impact of technology-enabled healthy food labels on online grocery shopping in impulsive and non-impulsive consumers - Ljusic, Nikola; Fagerstrøm, Asle; Sigurdsson, Valdimar; Arntzen, Erik (Frontiers in Nutrition, 2023)
Unhealthy food consumption is a problem for society, companies, and consumers. This article aims to contribute to research regarding such issues by investigating how technology-enabled healthy food labels can impact food choice in an online grocery store context. This study conceptualized unhealthy and healthy food choice as a matter of impulsivity problems. Three technology-enabled healthy food labels were derived based on variables that might impact self-control, and their influence on food choice was investigated. This study consisted of 405 participants; their impulsivity was measured using an adjusting delay task and investigated the effects of self-monitoring, pre-commitment, and social proof-based technology-enabled healthy food labels on food choice in a hypothetical online grocery shopping setting by using a choice-based conjoint experiment. The results show that self-monitoring, pre-commitment, and social proof-based labels had the most to least impact on food choice in that order. The results indicate that self-monitoring and pre-commitment labels had more impact on the choice for impulsive compared to non-impulsive participants. Similarly, the results indicate that social proof had more impact on choice for non-impulsive participants. These findings suggest that self-monitoring of previous healthy food choice might be more effective than pre-commitment based on discounts for healthy food products. However, these differences were minor. This has managerial implications as companies might increase their revenue by introducing self-monitoring labels. Future research should investigate these technology-enabled healthy food labels in real food purchase settings.